Expression of Pan-cytokeratin [Ae1/Ae3] in Oral Squamous Cell Carcinoma and Potential Malignant Oral Disorders A Comparative Systematic Review - H, Nanda Kumar; Narayan, Madhu; Rajkumar, Krishnan; Vasanthi, V (Asian Pacific Journal of Cancer Care, 2022)
Introduction: Intermediate filament and its prime role in the cytoskeleton involved in maintaining cell morphology, and is mainly observed in epithelial cells called as Cytokeratin. CKAE1/AE3 is a combination of two different clones of anti-CK monoclonal antibodies, a single reagent can be obtained with broad spectrum reactivity to high molecular weight and low molecular weight CK which can be used in different types of cancers or lesions. Aim: To compare the expression of the CK-AE1/AE3 in oral squamous cell carcinoma (OSCC) and potentially malignant oral disorders (PMOD) through immunohistochemical method through a systematic review process. Materials and Methods: Articles or original studies related to the use of IHC marker AE1/AE3 in OSCC, malignant tumors and PMODs were selected for systematic review process. PUBMED and GOOGLE SCHOLAR were the search engines used for collection of articles. Keywords used were PAN CK [AE1/AE3], SCC, OSCC, PMOD. Articles included based on PRISMA guidelines. Results: A total article based on search strategy identified 492 suitable abstracts; 474 did not meet the eligibility criteria. Full text articles were obtained for 18 articles. Six articles were excluded from the study for various reasons like case reports, reviews and letters to editors and any article published in languages other than English were also excluded. Finally, after considering all the inclusion and exclusion criteria, a total of 12 articles were included in the study. Considering all these articles, comparing the expression of pan-cytokeratin [ae1/ae3] in oral squamous cell carcinoma and potential malignant oral disorders.